Impact of the COVID-19 pandemic on cervical cancer screening participation, abnormal cytology prevalence and screening interval in Catalonia - Robles, Claudia; Monfil, Laura; Ibáñez, Raquel; Roura, Esther; Font, Rebeca; Peremiquel-Trillas, Paula; Brotons, Maria; Martínez-Bueno, Cristina; de Sanjosé, Silvia; Espinàs, Josep Alfons; Bruni, Laia (Frontiers in Oncology, 2024)
The COVID-19 pandemic led to a national lockdown and the interruption of all cancer preventive services, including cervical cancer screening. We aimed to assess the COVID-19 pandemic impact on opportunistic screening participation, abnormal cytology (ASCUS+) prevalence and screening interval in 2020 and 2021 within the Public Health System of Catalonia, Spain.Individual data on cytology and HPV testing of women aged 25-65 from 2014 to 2021 were retrieved from the Information System for Primary Care Services (SISAP). Time-series regression models were used to estimate expected screening participation and abnormal cytology prevalence in 2020 and 2021. The impact was determined by comparing observed and expected values (ratios). Additionally, changes in screening interval trends between 2014 and 2021 were assessed by fitting a Piecewise linear regression model.Cervical cancer screening participation decreased by 38.8% and 2.2% in 2020 and 2021, respectively, with the most significant impact on participation (-96.1%) occurring in April 2020. Among older women, participation was lower, and it took longer to recover. Abnormal cytology prevalence was 1.4 times higher than expected in 2020 and 2021, with variations by age (range=1.1-1.5). From June 2020 onwards, the screening interval trend significantly changed from an increase of 0.59 to 3.57 months per year, resulting in a median time of 48 months by December 2021.During the pandemic, fewer women have participated in cervical cancer screening, abnormal cytology prevalence has increased, and the screening interval is more prolonged than before. The potential cervical cancer lifetime risk implications highlight the need for organized HPV-based screening.